SYNTHESIS OF BIFUNCTIONAL CATALYSTS BASED ON MESOPOROUS ALUMINOSILICATES FOR HYDROAROMATIZATION OF MODEL COMPOUNDS - Abdrassilova Albina; Vassilina Gulzira (Academics and Science Reviews Materials, 2023)
Currently, new catalytic systems are being studied to address energy and environmental challenges. In the field of renewable energy, increasing the aromatic content of diesel fuels is an essential consideration because it lowers the fuel’s quality and can result in harmful emissions when burned [1]. One way to reduce the aromatic content is by converting aromatic compounds into cyclic alkanes. This can increase the cetane number of the fuel and improve its quality [2]. Mesoporous aluminosilicates promoted with nickel and molybdenum catalysts have shown promise in the hydroprocessing of aromatic hydrocarbons, contributing to their effectiveness and efficiency.